The Role of School Counselors in Preventing Bullying Against Visually Impaired Students in an Inclusive High School - Rizky Marulitua Sinaga; Nuraini; Rafael Lisinus Ginting (Cakrawala Sekolah: Journal of Multidisciplinary School Education, 2026)
Bullying remains a significant challenge in inclusive education, particularly for students with visual impairments who are more vulnerable to discrimination, social exclusion, and peer victimization. School counselors play a critical role in creating safe and supportive learning environments; however, their involvement in preventing bullying against visually impaired students has received limited scholarly attention. This study aimed to analyze the role of school counselors in preventing bullying against visually impaired students in an inclusive school setting at SMAN 2 Lubuk Pakam, Indonesia. A qualitative descriptive approach was employed to gain an in-depth understanding of counseling practices and bullying prevention efforts. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving a school counselor, school administrators, visually impaired students, and regular students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that school counselors performed several important roles, including providing emotional support, facilitating social interaction, and mediating conflicts involving visually impaired students. These interventions contributed to students’ psychological well-being and social adjustment. However, bullying prevention efforts remained largely reactive, as counseling services were primarily implemented after incidents occurred rather than through structured preventive programs. The study also identified the absence of systematic disability-awareness initiatives, peer-support programs, and empowerment-based interventions designed to strengthen students’ resilience and self-advocacy skills. The findings highlight the need for more comprehensive and sustainable bullying prevention strategies within inclusive schools. Strengthening school counselors’ preventive roles through anti-bullying programs, disability awareness education, and collaborative support systems is essential for fostering inclusive, safe, and equitable educational environments for students with visual impairments.